2009
DOI: 10.1007/s10875-008-9273-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Primary Immunodeficiencies in Thai Children: An 18-year Experience from a Tertiary Care Center

Abstract: These results provide clinical features of PID in Thailand. Knowing these features will lead to prompt diagnosis and appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
0
20
0
2
Order By: Relevance
“…Madkaikar et al reported 159 PID cases from a tertiary care center in India in 2013 followed by a more recent report describing 778 registered patients. Frequencies of PIDs were as follows: diseases of immune dysregulation (23.1%), phagocytic defects (21.3%) and predominant antibody deficiency Other registries were reported from Oman (140 patients with high proportion of patients with congenital defects of phagocyte 35%) [44], Taiwan (215 patients with 50.6% molecular diagnosis) [13], Malaysia (150 patients) [43,45], Thailand (67 patients) [46], Jordan (53 patients) [47], Singapore (39 patients) [48], UAE (30 patients) [49] and Bangladesh (13 patients) [50].…”
Section: Article Highlightsmentioning
confidence: 99%
“…Madkaikar et al reported 159 PID cases from a tertiary care center in India in 2013 followed by a more recent report describing 778 registered patients. Frequencies of PIDs were as follows: diseases of immune dysregulation (23.1%), phagocytic defects (21.3%) and predominant antibody deficiency Other registries were reported from Oman (140 patients with high proportion of patients with congenital defects of phagocyte 35%) [44], Taiwan (215 patients with 50.6% molecular diagnosis) [13], Malaysia (150 patients) [43,45], Thailand (67 patients) [46], Jordan (53 patients) [47], Singapore (39 patients) [48], UAE (30 patients) [49] and Bangladesh (13 patients) [50].…”
Section: Article Highlightsmentioning
confidence: 99%
“…All countries that participated in the first publication in 1998 reported an increase of PID cases, ranging between 10% and 80%. 24 These two reports highlight that, predominantly, antibody deficiencies remain the main PIDs registered in Latin America, with similar trends in other countries such as Australia, 37,38 China, 39,40 Egypt, 41 France, 42 Hong Kong, 43 Iran, [44][45][46] Italy, 47 Kuwait, 48 the Netherlands, 49 Norway, 50 Poland, 51 Republic of Ireland, 52 Spain, 53,54 Switzerland, 55 Taiwan, 56 Thailand, 57 Tunisia, 58 and the United States. 59,60 However, other well-defined PID syndromes, such as ataxia-telangiectasia, have been reported more frequently, especially in Mexico and Central America.…”
Section: Lasid Activitiesmentioning
confidence: 72%
“…Brazil reported 50 cases of deficiency complement, followed by 13 reports of Argentina (Leiva et al, 2007). Like others studies, predominantly antibody deficiency was the principal PID observed in Latin America, Australia (Baumgart et al, 1997;Kirkpatrick et al, 2007), China (Zhao et al, 2006;Wang et al, 2011), Egypt (Reda et al, 2009), French (CEREDIH, 2010, Hong Kong (Lam et al, 2005), Iran (Aghamohammadi et al, 2002;Farhoudi et al, 2005;Rezaei et al, 2006), Italy (Luzi et al, 1983), Kuwait (AlHerz, 2008), Netherland (Zegers et al, 1994), Norway (Stray-Pedersen et al, 2000), Poland (Bernatowska et al, 1998), Republic of Ireland (Abuzakouk et al, 2005), Spain (Matamoros et al, 1997;Milá et al, 2001), Swiss (Ryser et al, 1998), Taiwan (Lee et al, 2011), Thailand (Benjasupattananan et al, 2009), Tunisia (Bejaoui et al, 1997) and USA (Javier et al, 2000;Stiehm, 2007), Studies in other countries reveled major number of granulocyte dysfunction in India (Verma et al, 2008), and Combined T-and B-cell Immunodeficiency in Turk (Shabestari et al, 2007).…”
Section: Latin American Group Of Immunodeficiencymentioning
confidence: 99%